Clinical Commentary: A Criteria-Based Testing Protocol for Return to Sport Post Hip Arthroscopy for Impingement - Gabriella Hugenberg; Jason Stallons; Chad Smith; Kathryn Brockhoff; Matthew Gingras; Darryl Yardley; Olufemi Ayeni; Mahmoud Almasri (North American Sports Medicine Institute, 2023)
Overall, 84%-87% of athletes will return to sport following hip arthroscopy; however, some literature suggests that only 57% of athletes return to their preinjury level, and only 16.9% report optimal performance. This discrepancy may be due to a lack of consistency within the definition of return to sport as well as a lack of consistency within rehabilitation programs when determining return to sport readiness. Athletes who are returning to sport must demonstrate adequate range of motion, strength, and the ability to perform multi-directional movements without the risk of reinjury. There has yet to be a comprehensive, criteria-based, return to sport testing protocol that utilizes objective measures to ensure athletes are ready for return to sport. The goal of the authors was to create a criteria-based testing protocol for return to sport following hip arthroscopy utilizing components best supported in the literature. The following parameters were identified as key areas to assess for within a return to sport testing protocol: range of motion, strength, functional testing, self-reported outcomes including psychological readiness and time. The purpose of this clinical commentary is to propose a criteria-based testing protocol to be used following hip arthroscopy for impingement from early rehabilitation through return to previous level of sport. Criteria are presented clearly to promote objective progression through rehabilitation while still being mindful of the biological healing time required for safe and efficient progression. It is the authors' hope that in identifying and establishing a criteria-based testing protocol a higher percentage of athletes will be able to return to sport. # Level of Evidence 5